Electrochemical oxidation of nitrogen towards direct nitrate production on spinel oxides - Dai, Chencheng (2022)
Nitrates are widely used as fertilizer and oxidizing agents. Commercial nitrate production from nitrogen involves high-temperature-high-pressure multi-step processes. Therefore, an alternative nitrate production method under ambient environment is of importance. Herein, an electrochemical nitrogen oxidation reaction (NOR) approach is developed to produce nitrate catalyzed by ZnFex Co2-x O4 spinel oxides. Theoretical and experimental results show Fe aids the formation of the first N-O bond on the *N site, while high oxidation state Co assists in stabilizing the absorbed OH- for the generation of the second and third N-O bonds. Owing to the concerted catalysis, the ZnFe0.4 Co1.6 O4 oxide demonstrates the highest nitrate production rate of 130±12 μmol h-1  gMO -1 at an applied potential of 1.6 V versus the reversible hydrogen electrode (RHE).